Study of histopathological pattern of endometrium in abnormal uterine bleeding in a tertiary care center - Shinde, Pratibha T.; Sarate, Dilip S.; Patil, Suwarna B.; Patil, Bhupendra V.; Kangate, Swarada V. (International Journal of Research in Medical Sciences, 2023)
Background: It is estimated that 9-30% of women of reproductive age suffer from abnormal uterine bleeding. As most cases are associated with anovulatory menstrual cycles, adolescent and perimenopausal women are particularly vulnerable to this particular condition. The aim of this study was to evaluate the histopathological pattern of endometrial biopsy from patients presenting with abnormal uterine bleeding. Methods: The retrospective study was conducted in the Department of Pathology in tertiary care centre from 1st January 2021 to 31 December 2022. All the patients presenting with abnormal uterine bleeding and who underwent endometrial biopsy were included in this study. Distribution of various histopathological patterns was observed in the different age groups. Results: A total of 260 cases were included in the study. The commonest pattern in these patients was proliferative endometrium (31 %) and products of conception (31%), hyperplasia without atypia (13.7%). Other patterns identified were secretory endometrium, chronic endometritis, endometrial polyp, complete mole, partial mole, and Ca endometrium. Conclusions: As observed from the study, there is an age specific association of endometrial bleeding, with highest incidence in 21-30 years of age group. Hence, dilatation and curettage are helpful for diagnosis, to assess therapeutic response and to know the pathological incidence of organic lesions in cases of abnormal uterine bleeding.